Sustainable purchasing decisions for halal cosmetics in Indonesia - Robani, Anidah; Mas Soeroto, Wisudanto; Widiastuti, Tika; Mardhiyah, Dien; Mawardi, Imron; Ningsih, Sri; Al Mustofa, Muhammad Ubaidillah (Universiti Malaysia Terengganu, 2023)
Halal cosmetics have become a sustainable industry, particularly in Muslim countries such as Indonesia. This study analyses factors influencing consumer purchasing decisions for halal cosmetics in Indonesia through two samples: millennials and non-millennials. This quantitative study used a Partial Least squares structural equation modelling (PLS-SEM) analysis on 211 respondents’ data. Of the 211 respondents, 109 are Millennials, and 102 are from the Boomer and Generation X generations. The variables used in this study are the halal label, price fairness, budget allocation, and perceived value. Halal labelling and price fairness are important factors in determining whether consumers buy halal cosmetics. The variable of price fairness has the most substantial influence. It has a greater impact on millennials than on non-millennials. Simultaneously, the importance of the halal label is more notable for the Boomers and Generation X than for the Millennials. This study confirms that the halal label influences the purchasing of halal cosmetics across different generations. The concern about halal cosmetics is more profound for Boomers and Generation X than Millennials. On the other hand, price fairness is more notable among millennials than in older generations.